Transparent body colored glass-ceramic-containing product
Patent Information
- Application Number
- JP2022104552
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2021-06-29
- Filing Date
- 2022-06-29
- Publication Date
- 2025-03-11
AI Technical Summary
Existing transparent body-colored glass-ceramics used in kitchen and laboratory fixtures face challenges in achieving high brightness and color neutrality across multiple light colors, particularly with blue, red, and white light, while maintaining thermal, chemical, and mechanical integrity, and are often incompatible with different lighting systems, leading to safety issues and high costs due to the use of color correction filters with limited temperature stability.
A transparent, body-colored glass-ceramic composition comprising specific oxide percentages of SiO2, Al2O3, Li2O, TiO2, ZnO, and MoO3, with controlled luminous transmittance and color locus in the white region of the CIExyY chromaticity diagram, ensuring minimal color shift and compatibility with various lighting systems.
The solution provides a glass-ceramic with high color neutrality, maintaining brightness and safety by minimizing color shifts, reducing operational hazards, and improving economic efficiency by eliminating the need for expensive color correction filters.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
[Technical Field]
[0001] This invention relates to a product characterized by a transparent, volume-colored glass-ceramic body, and to the use thereof.
[0002] Products featuring transparent, colored glass-ceramic bodies are used in a variety of applications, such as kitchen and laboratory fixtures and accessories. Glass-ceramic sheets are used, for example, as viewing windows on baking oven doors, as cover panels for the operating elements of cooking appliances, or as worktops for kitchen cabinets and laboratory equipment, and are used in both household and commercial settings. Such articles often have lighting systems that include multiple light-emitting elements, which are provided, for example, to indicate the operating status or for decorative lighting purposes, by illuminating through the glass-ceramic sheet.
[0003] In particular, the technical requirements are becoming increasingly complex for lighting systems, which are part of the user interface of such items. The key points in these cases are always ease of use for the user and enhanced safety of operation. At the same time, the glass-ceramic sheets used for this purpose must possess maximum versatility so that they can be combined with almost any conceivable type of lighting system.
[0004] An example of this type of complex requirement imposed on lighting systems for user interfaces is the use of multiple light colors to represent different functions. In this case, all colors must be able to be represented at high brightness. Blue, red, and white light are particularly preferred for this purpose.
[0005] Another example is using different brightness levels of lighting to highlight active parts of a user interface compared to inactive parts, for example, to facilitate user interaction. In such cases, the active parts can be displayed brighter than the inactive parts.
[0006] At the same time, glass-ceramic products must also meet the remaining requirements for their intended use, such as thermal, chemical, and mechanical integrity, or opacity to prevent the interior of the article from being seen.
[0007] Prior art examples include transparent colored glass-ceramic body plates used as cover plates for kitchen appliances. Colored glass-ceramic body plates for kitchen appliances generally contain vanadium ions for coloring. This is because these ions have the unique property of absorbing in the visible light region and exhibiting high transmittance in the infrared radiation region. This type of coloring with V2O5 is known, for example, from German Patent Application Publication No. 102008050263.
[0008] The increase in transmittance of the vanadium-colored glass-ceramic body begins not only in the near-infrared region but also in the red portion of the visible spectrum. Therefore, for red light, they have several times higher transmittance than, for example, blue light.
[0009] A variety of transparent, colored glass-ceramic bodies for kitchen appliances are commercially available, and they can be classified into two categories based on their optical properties.
[0010] These dark-colored glass-ceramic plates are 4mm thick and have a visible light transmittance of approximately 0.5% to 3.5%. Due to their low light transmittance, these plates effectively prevent the inside of the stove from being visible.
[0011] These are light-colored glass-ceramic plates with a thickness of 4mm and a visible light transmittance of approximately 3.5% to 6%. Due to their high light transmittance, this type of glass-ceramic plate usually requires an opaque layer on the underside to prevent the inside of the stove from being seen. Because of their overall high transmittance, they are in principle suitable for use with red or blue lighting systems. However, they are not automatically compatible with lighting systems for dark-colored glass-ceramic plates, as they can appear dazzling and, in the worst case, reduce operational safety due to their opaque effect.
[0012] It is also known from the prior art that these types of glass-ceramic plates can be combined with color correction filters to enable the use of white lighting systems. However, generally speaking, such optical filters have limited temperature stability and are relatively expensive.
[0013] German Utility Model Publication No. 202018102537 discloses articles of equipment and fixtures characterized by a transparent, colored glass-ceramic substrate. The main coloring agent of the glass-ceramic is MoO3, which has a luminous transmittance of 0.1% to 12%. The color trajectory of the glass-ceramic extends along a blackbody curve in the white region W1 in the CIEyxY color space.
[0014] The object of the present invention is to provide a product including a transparent body-colored glass-ceramic in which the color trajectory of the glass-ceramic is particularly color-neutral. At the same time, it is necessary to improve economic efficiency compared to glass-ceramics known from the prior art.
[0015] This objective is achieved by the subject matter of the independent claim. Specific and preferred embodiments are specified in the dependent claims.
[0016] Therefore, the present invention is a product comprising a transparent body-colored glass-ceramic, wherein the glass-ceramic contains the following components in weight % based on oxides: SiO2 58 - 72, Al2O3 16 - 26, Li2O 1.0 - 5.5, TiO2 2.0 - <4.0, ZnO 0 - <2.0, MoO3 0.005 - 0.12, and the glass-ceramic has a visual transmittance τ of 0.5% - 3.5% based on a thickness of 4 mm vis and the glass-ceramic has, based on a thickness of 4 mm, after light from the standard light source D65 passes through the glass-ceramic, the following coordinates:
Table 1
[0017] This type of product may be, for example, an article of equipment or facility for a kitchen or a laboratory. For the purposes of the present invention, this generally means an article suitable for supplying or installing in a kitchen or a laboratory. These are more specifically kitchen or laboratory equipment, or kitchen or laboratory electrical appliances, and are preferably electrically operated regardless of their specific structural forms. Kitchen and laboratory equipment particularly includes cupboards and workbenches having a worktop on the upper surface. Kitchen electrical appliances such as cooking appliances, refrigerators, microwave ovens, grills, baking ovens, steam cookers, toasters, or ventilation fans in this specification may be designed for either household or business use. The article may be an independent operation panel by which a user can operate one or more electrical appliances controllable by a panel. The electrical appliances of the present invention may be, for example, incorporated into kitchen or laboratory equipment, or may be of an independent type. Laboratory electrical appliances particularly include ovens, air-conditioning cabinets, refrigerators, or hot plates.
[0018] The product may be a stove, more specifically a stove window, and the inner lining of the stove, a heat lamp, more specifically a cover or an infrared heat lamp, a mobile electronic device such as a mobile phone or a tablet computer, or an automobile, more specifically an operation panel or a display panel of an automobile, or may include fireproof glass.
[0019] Another example of the product of the present invention is a stove having a glass-ceramic cooking plate, and the stove includes a display device and, for example, a heating element, more specifically an induction heating element. A viewing window of a baking oven door or a microwave oven door is also a product of the present invention. In kitchen or laboratory equipment, such a product may be at least a part of the main body of the equipment, or the front surface, door, or drawer. It is particularly preferable that the product as a cover plate constitutes part or even the whole of the worktop of an article of kitchen or laboratory equipment.
[0020] The product of the present invention includes a transparent body-colored glass-ceramic. The transparent glass-ceramic herein is a glass-ceramic with little visible light scattering. The body-colored glass-ceramic in the meaning of the present invention is a glass-ceramic having a visual transmittance of less than 80% and containing a single or a plurality of oxides of transition metals from Group 5 to Group 11 of the periodic table as coloring components. This particularly includes V2O5, Cr2O3, Fe2O3, CoO, NiO, CuO, and MoO3. Other specific chemical elements may also act as colorants for the glass-ceramic, and an example is an oxide of a lanthanoid, more specifically Nd2O3. As a result of these coloring components, the glass-ceramic absorbs light. Based on this absorption, the visual transmittance is less than 80%. For the operation of manufacturing the glass-ceramic, the components are substantially uniformly distributed in the glass-ceramic. Therefore, the coloring components uniformly color the volume of the glass-ceramic.
[0021] This distinguishes transparent, colored glass-ceramic materials from opaque glass-ceramics, which exhibit reduced light transmittance due to greater scattering of visible light. The light scattering in opaque glass-ceramics is a result of the number, size, and refractive index of crystals within the glass-ceramic. Therefore, this is a consequence of the microstructure of the glass-ceramic.
[0022] Transparent colored glass-ceramics differ from uncolored transparent glass-ceramics in that they have a low luminous transmittance. Uncolored glass-ceramics have a luminous transmittance of over 80%. They contain coloring components only as unavoidable impurities, or in very small amounts, based on the raw materials used in their manufacture, or to fine-tune the optical properties of uncolored transparent glass-ceramics.
[0023] The glass-ceramic product of the present invention contains 58% to 72% by weight of SiO2, 16% to 26% by weight of Al2O3, and 1.0% to 5.5% by weight of Li2O. These three components are essential in these amounts to establish the typical microstructure of lithium aluminum silicate glass-ceramics and enable the associated low thermal expansion.
[0024] The glass-ceramic product of the present invention preferably contains 60% to 70% by weight of SiO2, 18% to 24% by weight of Al2O3, and 2.5% to 5% by weight of Li2O. More preferably, the glass-ceramic product of the present invention contains 62% to 68% by weight of SiO2, 19% to 23% by weight of Al2O3, and 3% to 4.5% by weight of Li2O. Within these preferred ranges, a typical microstructure and the resulting low thermal expansion can be obtained particularly easily and particularly stably in industrial production.
[0025] Since Li2O is one of the essential components of the crystalline phase of glass-ceramics, the proportion of Li2O has a significant impact on the thermal expansion of glass-ceramics. The lower the amount of Li2O, the lower the volume fraction of the crystalline phase in the glass-ceramics. As a result, thermal expansion increases. At the same time, lithium is a strategically important raw material for the manufacture of glass-ceramics. The high demand for lithium from battery manufacturers greatly affects the amount of lithium available and its price. Therefore, for products where the requirements for thermal cycle stability are not so stringent, it is advantageous to use glass-ceramics with the lowest possible proportion of Li2O, more specifically, glass-ceramics with a Li2O proportion in the range of 1.2% to 3%, preferably 1.3% to 2.5%, and even 1.5% to 2%.
[0026] The glass-ceramic product of the present invention further comprises 2.0 wt% to <4.0 wt% TiO2, 0 wt% to <2.0 wt% ZnO, and 0.005 wt% to 0.12 wt% MoO3.
[0027] TiO2 significantly influences nucleation during ceramicization. Therefore, it plays an important role in the production of glass-ceramics. Since the color effect of molybdenum oxide is also supported by the amount according to the present invention, that is, the addition of TiO2 in the presence of MoO3 results in a low light transmission value, the present invention requires a minimum level of 2.0 wt% in the glass-ceramics. A preferred minimum level is 2.5 wt%, more preferably 2.8 wt%, and even further 3.0 wt%. However, TiO2 adversely affects devitrification stability. As a result, the amount of TiO2 is less than 4.0 wt%. To further improve devitrification stability, the amount of TiO2 is preferably 3.9 wt% or less, and even further 3.8 wt% or less. Therefore, in a preferred embodiment, the glass-ceramics, like the other components, contain an amount of TiO2 of 2.5 wt% to <4.0 wt%, preferably 2.8 wt% to 3.9 wt%, and more preferably 3.0 wt% to 3.8 wt%.
[0028] Surprisingly, in the production of MoO3-containing glass-ceramics in commercial continuous melting units, ZnO was found to have a particularly strong influence on both the resulting microstructure and the coloration of the glass-ceramics.
[0029] Therefore, according to the present invention, the ZnO content of the glass-ceramic is strictly limited to less than 2% by weight, preferably to a maximum of 1.9% by weight, and more preferably to a maximum of 1.8% by weight. However, in small amounts, ZnO helps to develop glass-ceramic microstructures that are particularly advantageous to the present invention. Therefore, the glass-ceramic contains preferably at least 0.1% by weight, more preferably at least 0.5% by weight, more specifically at least 1.0% by weight, and even more preferably at least 1.2% by weight of ZnO.
[0030] The products of the present invention are further characterized in that, in combination with the above components, the glass-ceramic contains MoO3 in an amount of 0.005% to 0.12% by weight. In one variant of the present invention, the glass-ceramic contains 0.015% to 0.100% by weight, preferably 0.020% to 0.080% by weight, and more preferably 0.030% to 0.070% by weight. Since different valencies of Mo atoms may be expressed in the glass-ceramic, the specified content of the composition is based on the compound MoO3 for analytical purposes.
[0031] A minimum level of 0.005 wt% MoO3 combined with other components in their respective amounts is sufficient to achieve the desired color effect and transmittance. Higher MoO3 levels, up to 0.12 wt%, are required when aiming to achieve lower light transmittance. Similarly, both Fe2O3 and V2O5 alter the transmission properties of the glass-ceramic, causing the color coordinates of the light from a standard light source D65 after passing through the glass-ceramic to shift away from the blackbody curve, more specifically towards the red phase. Therefore, when adding Fe2O3 or V2O5, higher MoO3 levels of up to 0.12 wt% tend to be required. This effect can be at least partially compensated for by the addition of MoO3.
[0032] At amounts of 0.12% by weight or less, MoO3, more specifically reduced molybdenum oxide species, do not exhibit a nucleating agent effect and therefore do not significantly affect devitrification stability.
[0033] To obtain a color effect, preferably, at least 0.015% by weight, more preferably at least 0.020% by weight, and very preferably at least 0.030% by weight of MoO3 is present. As an upper limit, the MoO3 content is preferably 0.100% by weight, more preferably 0.080% by weight, and very preferably 0.070% by weight.
[0034] When the ratio of MoO3 to TiO2, i.e., MoO3 / TiO2, is 0.002 to 0.050, preferably 0.004 to 0.040, and more preferably 0.008 to 0.030, it is possible to achieve a particularly accurate luminous transmittance using a particularly small amount of MoO3.
[0035] Furthermore, the glass-ceramic product of the present invention has a luminous transmittance τ of 0.5% to 3.5%, preferably 0.8% to 3.2%, more preferably 1.0% to 3.0%, and more specifically 1.2% to 2.8%, based on a thickness of 4 mm. vis It has.
[0036] Luminous transmittance τ vis This refers to the degree of light transmission measured in the visible spectral range of 380–780 nm in accordance with DIN EN 410. This value is a measure of the sensitivity of the human eye to light. This value is equivalent to the lightness Y in the CIExyY color space, measured by transmittance.
[0037] In this specification, "based on a thickness of 4 mm" means that the value is measured for a glass-ceramic thickness of preferably 4 mm. If the glass-ceramic thickness is other than 4 mm, the transmission spectrum of the glass-ceramic at the existing thickness is measured and converted to a thickness of 4 mm by the Beer-Lambert law. The luminous transmittance is then determined according to DIN EN 410 using this spectrum converted to 4 mm.
[0038] The glass-ceramic material of the product is transparent. Therefore, scattering of visible light is negligibly small. Consequently, it is not important to the measurement results whether an Ulbricht sphere is used to measure transmittance or whether the measurement is performed from an observation angle of only 2°. Diffuse transmittance is negligibly small compared to direct transmittance. Therefore, the measured luminous transmittance of the substrate body with and without an Ulbricht sphere will differ by up to 10%, preferably up to 1%, and even less than 0.5%, based on the value measured with an Ulbricht sphere.
[0039] Based on a thickness of 4mm, the luminous transmittance τ vis Glass-ceramic materials with a crystalline content of 0.5% to 3.5% exhibit varying opacity under normal ambient light, depending on their actual thickness. Normal ambient light includes, for example, daylight or lighting of similar brightness. However, at the same time, the glass-ceramic material is bright enough for a light-emitting display to be visible through it at an appropriate brightness.
[0040] Particularly advantageous is that this makes it possible to provide products with user interfaces that have at least one luminescent display. This type of luminescent display, in this case, is visible through the glass-ceramic when switched on, but invisible when not in operation. This is particularly advantageous, for example, for kitchen appliances or cooking surfaces where the display is only visible when in operation. This improves operational safety and consequently enhances the operational reliability of kitchen appliances, which could otherwise be prone to misconfiguration.
[0041] For example, the thickness of the glass-ceramic cooking surface is typically 3-7 mm. The thickness of the cooking surface is usually around 4-6 mm.
[0042] Based on a thickness of 4 mm, the glass-ceramic product of the present invention, after light from a standard light source D65 passes through the glass-ceramic, shows the following coordinates: [Table 2] It has the characteristic of having a color locus in the white region A1 of the CIExyY-2° chromaticity diagram defined by [the specified method].
[0043] The light from the standard light source D65 has, by definition, a color temperature of approximately 6500K and a color locus of x=0.3127 and y=0.3290 when viewed directly by an observer at 2°.
[0044] This glass-ceramic material, which exhibits the characteristic that light from a standard light source D65 has a color locus of x=0.3127 and y=0.3290 after passing through it, is perfectly chromatically neutral. It does not alter the color of light passing through it. (Color shift)
number
[0045] The term "light" always refers to visible light in the wavelength range of 380 nm to 780 nm, unless otherwise specified or explained.
[0046] All glass-ceramics in the products of this invention are C to the light of a standard light source D65. * It exhibits particularly high color neutrality, resulting in a color shift of ≤0.08. Therefore, the white region A1 is noteworthy for the particularly high color neutrality of the glass-ceramic components it contains.
[0047] In this specification, the white region A1 is a region along the blackbody curve in the CIExyY color space with a color temperature range of approximately 4500K to approximately 9000K, shifted upward by approximately y=0.03 at the upper boundary and downward by approximately y=0.04 at the lower boundary relative to the blackbody curve. Thus, in this invention, when white light passes through the glass-ceramic, the color trajectory of the light can be essentially shifted along the blackbody curve both toward higher color temperatures (e.g., 6500K to 9000K) and toward lower color temperatures (e.g., 6500K to 4500K) without producing undesirable color hues. As a result, the white light is still perceived as white light even after passing through.
[0048] The color locus of light can be measured, for example, with a Konica Minolta CS-150 colorimeter. Similarly, to calculate the color locus, the transmission spectrum of glass-ceramics can be measured and used, according to CIE specifications, using the known spectrum of the D65 standard light and the visual sensitivity of a standard observer of 2°.
[0049] In one preferred embodiment, the glass-ceramic product, based on a thickness of 4 mm, receives light from a standard light source D65 after passing through the glass-ceramic, at the following coordinates: [Table 3] It has the characteristic of having a color locus in the white region A2 of the CIExyY-2° chromaticity diagram defined by [the specified method].
[0050] All glass-ceramics with this property are C rated for light from the standard light source D65. * Because it produces only a color shift of ≤0.05, it exhibits remarkable uniform color neutrality. Furthermore, after passing through this type of preferred glass-ceramic, white light lies particularly close to the blackbody curve and is therefore perceived as particularly white by the human eye.
[0051] A further characteristic of glass-ceramics is the amount of dissolved oxygen, i.e., oxygen present in the glass-ceramic in the form of oxygen not covalently bonded to the glass matrix. The amount of dissolved oxygen is due to the melting process used in manufacturing. This can be affected in various ways. For example, the higher the melting temperature and clarification temperature, the less oxygen there is in the glass-ceramic. At high temperatures, the viscosity of the glass melt decreases, so bubbles that form can escape from the glass-ceramic more easily.
[0052] The oxygen content may also be affected by the properties and amount of the clarifying agent, or by the addition of a reducing agent. Examples of reducing agents include easily oxidizable metals, sulfides, or carbon, more specifically, Al or Si powder, sugar, charcoal, SiC, TiC, MgS, or ZnS. These are oxidized in the melt, and as a result, oxygen is removed from the melt until it is depleted. This results in a glass-ceramic with a relatively low dissolved oxygen content.
[0053] The amount of dissolved oxygen in glass-ceramics can be measured electrochemically, as is customary. This is comprehensively described, for example, in the publication "Developing a Probe for Measuring Oxygen Partial Pressure in Glass-melting tanks," Frey, T.; Schaeffer, HA; Baucke, FG in Glastechnische Berichte; 53, 5; 116-123, 1980. In short, first, fragments of glass-ceramics are melted in a suitable container. Then, a temperature-stable measuring electrode, such as one made of platinum, and a solid electrolyte, such as one made of yttrium-stabilized ZrO2, which has high conductivity for oxygen ions but low conductivity for electrons, are added to the melt. Subsequently, the oxygen partial pressure is determined as a function of the temperature of the molten glass using the electrode. As the temperature rises, dissolved oxygen is released from the glass-ceramic, and this pressure increases continuously with increasing temperature. The temperature at which the oxygen partial pressure determined in this way reaches 1 bar is called T(pO2=1bar). The more oxygen present in the glass-ceramic solution, the lower the temperature T(pO2=1bar) at which an oxygen partial pressure of 1 bar is achieved. Therefore, T(pO2=1bar) is a glass-ceramic property that indicates the amount of dissolved oxygen in the glass-ceramic.
[0054] When no reducing agent is used in the manufacture of glass-ceramics, the temperature T (pO2=1 bar) corresponds to the highest temperature reached during melting and / or clarification. When a reducing agent is used, the temperature T (pO2=1 bar) is higher than the highest temperature reached during melting or clarification.
[0055] In one advanced form of the present invention, the glass-ceramic product has a temperature T (pO2=1 bar) in the range of 1550°C to 1700°C, preferably 1560°C to 1690°C, and more preferably 1570°C to 1680°C. This temperature is a physical property of the glass-ceramic and represents a measured value of oxygen dissolved in the glass-ceramic. The higher the value of temperature T (pO2=1 bar), the less oxygen is present in the glass-ceramic solution.
[0056] Surprisingly, it was found that above temperatures T (pO2 = 1 bar) exceeding 1550°C, the coloring effect of MoO3 increased to such an extent that only a particularly small amount of MoO3 was needed to achieve a low luminous transmittance of less than 3.5%. This is particularly economically advantageous, as MoO3 is a relatively expensive component of glass-ceramics.
[0057] Preferably, temperatures T(pO2=1 bar) exceeding 1700°C, more preferably exceeding 1690°C, and very preferably exceeding 1680°C should be avoided. If T(pO2=1 bar) is relatively high, it is necessary to use a correspondingly high temperature during melting or to use a large amount of reducing agent. However, if the melting temperature is too high, it will negatively affect the service life of the melting tank and require more frequent maintenance. Furthermore, both factors are economically disadvantageous due to the energy and material costs required.
[0058] The addition of polyvalent components such as Fe2O3, MnO2, V2O5, CeO2, and TiO2 to glass-ceramics affects many different properties of the glass-ceramic. For example, certain polyvalent components may have a unique color effect, while others may act as clarifying agents or affect crystal formation. Some of these may act on two or more properties simultaneously, such as Fe2O3, which can cause coloration while simultaneously affecting clarity.
[0059] ZrO2 as a component of glass-ceramics is also favorable for nucleation. For this purpose, it is preferably present in the glass-ceramics in an amount of 0.1% to 2.5% by weight, more preferably 0.3% to 2.0% by weight, and very preferably 0.5% to 1.5% by weight.
[0060] Surprisingly, it was found that the ratio of ZrO2 to TiO2 affects not only nucleation but also the temperature stability of the color neutrality of the glass-ceramic. Glass-ceramics containing ZrO2 and TiO2 with a ZrO2 / TiO2 ratio of at least 0.1, preferably at least 0.15, more preferably at least 0.2, and up to 0.67, preferably up to 0.4, more preferably 0.33 exhibit improved optical stability under thermal load. Using the correspondingly selected ratio, it is possible to reduce, or even largely eliminate, the darkening, brightening, or shift of the color trajectory after operation in a stove with a radiant heating element.
[0061] Therefore, in another preferred embodiment, the glass-ceramic is typically, or combined with the above preferred amounts of ZrO2 and TiO2, with a ZrO2 / TiO2 ratio in the range of 0.1 to 0.67, preferably 0.15 to 0.4, and more preferably 0.2 to 0.33.
[0062] Furthermore, it is advantageous for the glass-ceramic to contain one or more of the following components in precisely specified amounts: V2O5, Cr2O3, Fe2O3.
[0063] Since even very small amounts of V2O5 cause a shift in the color trajectory, the color trajectory can be finely adjusted by using it in combination with the above-mentioned MoO3 component as appropriate. For this purpose, the glass-ceramic may contain 0.0001% to 0.010% by weight, preferably 0.0005% to 0.0080% by weight, and more preferably 0.0010% to 0.0050% by weight of V2O5. V2O5 is typically present in the glass-ceramic as an impurity in amounts of 1 to 15 ppm. Lower levels are only achievable by using raw materials purified through costly procedures, which are very expensive and labor-intensive.
[0064] Cr2O3 is added to the glass-ceramic of the present invention, and it has been shown that even in very small amounts, it strongly affects the color trajectory, more specifically the y-coordinate of the color trajectory of the glass-ceramic in transmission. When Cr2O3 is added, the value of the y-coordinate increases as desired. To fine-tune the color trajectory, the glass-ceramic contains 0% to 0.0100% by weight, preferably 0.0005% to 0.0090% by weight, and more preferably 0.0010% to 0.0060% by weight. Cr2O3 is usually present in glass-ceramic as an unavoidable impurity in amounts of 1 to 5 ppm.
[0065] Furthermore, when V2O5 was added simultaneously with the above-mentioned amount of Cr2O3, an unexpected interaction was revealed. By adding V2O5 and Cr2O3 simultaneously, the x-coordinate of the color trajectory can be adjusted to the desired value. The greater the amount of V2O5 and Cr2O3 present simultaneously in the glass-ceramic, the higher the value of the x-coordinate. For this purpose, the glass-ceramic may optionally contain 0.001 to 0.010, preferably 0.002 to 0.008, and more preferably 0.0025 to 0.0065 of V2O5 + Cr2O3.
[0066] When MoO3 is used as the main coloring agent, particularly excellent color neutrality can be achieved in glass-ceramics containing MoO3, V2O5, and Cr2O3 in a ratio (V2O5 + Cr2O3) / MoO3, preferably in the range of at least 0.005 to 0.5, preferably at least 0.01 to 0.2, and more preferably at least 0.03 to 0.15. Within this ratio range, the effects of these three components are balanced, resulting in a glass-ceramic with particularly excellent color neutrality.
[0067] Furthermore, it was found that the production of glass-ceramics in a continuous melting unit is particularly advantageous when the composition of the glass-ceramics satisfies the following condition: Li2O + SnO2 < 5.8, preferably < 5.0, and more preferably < 4.5.
[0068] Fe2O3 has a strong influence on transmittance, particularly in the near-infrared spectral range, and reduces the coloring effect of MoO3 in the visible spectral range. To fine-tune the infrared transmittance in particular, the glass-ceramic may contain 0.05% to 0.3% by weight, preferably 0.06% to 0.2% by weight, and more preferably 0.07% to 0.15% by weight of Fe2O3.
[0069] The MnO2 component reduces discoloration caused by MoO3. Therefore, the MnO2 content is preferably less than 0.5% by weight, more preferably less than 0.1% by weight, and even more preferably less than 0.05% by weight. Since MnO2 can have an assisting effect during the clarification stage, it can be present in the glass-ceramic in an amount of preferably more than 0.001% by weight, and more preferably more than 0.005% by weight.
[0070] The glass-ceramic preferably contains 0% to 0.4% by weight, more preferably 0% to 0.2% by weight of Nd2O3. More specifically, the Nd2O3 content may be 0% to 0.06% by weight. It is particularly preferable that Nd2O3 is not used and that Nd2O3 is not technically present in the glass-ceramic due to unavoidable impurities. In that case, impurities are usually present at less than 10 ppm. In this colored oxide, the color effect is produced by a narrow absorption band in the wavelength range of 526, 584, and 748 nm. Light in this wavelength range is absorbed more strongly when passing through the glass-ceramic.
[0071] A first preferred glass-ceramic composition for the product of the present invention is, in weight percent based on oxides, essentially consisting of the following: Li2O 1.0~5.5, Al2O316~26, SiO258~72, TiO2 2.0~<4.0 ZrO2 0.1~2.5 ZnO 0~<2.0, SnO2 0.05~<0.7 MoO30.005~0.12, Fe2O3 0.05~0.30 Cr2O30 ~ 0.0100, V2O50.0001~0.010.
[0072] In this composition, it may be particularly advantageous to select a proportion of MoO3 in the range of 0.015% to 0.100% by weight, preferably 0.020% to 0.080% by weight, and more preferably 0.030% to 0.070% by weight, and to select other components within the above range.
[0073] Particularly advantageous properties can be achieved when the first preferred composition is selected within the following range: Li2O 2.5~5 Al2O3 18~24 SiO260~70 TiO2 2.5 ~ <4.0 ZrO2 0.3~2.0 ZnO 0.1~1.9 SnO2 0.06 ~ <0.6 MoO30.015~0.100 Fe2O3 0.06~0.20 Cr2O3 0.0005~0.0090 V2O50.0005~0.0080.
[0074] Particularly advantageous properties can be achieved when the first preferred composition is selected within the following range: Li2O 3~4.5 Al2O3 19~23 SiO262~68 TiO2 2.8~3.9 ZrO2 0.5~1.5 ZnO 0.5~1.8 SnO2 0.07~<0.5 MoO30.020~0.080 Fe2O3 0.07~0.15 Cr2O3 0.0010~0.0060 V2O50.0010~0.0050.
[0075] A second preferred glass-ceramic composition for the product of the present invention is an oxide-based composition, in weight percent, essentially consisting of the following: Li2O 1.0~5.5 ΣNa2O+K2O 0.1~<4 MgO 0~3 ΣCaO+SrO+BaO 0~5 ZnO 0~<2.0 B2O30~3 Al2O3 16~26 SiO258~72 TiO2 2.0 ~ <4.0 ZrO2 0.1~2.5 SnO2 0.05 ~ <0.7 P2O50~4 MoO30.005~0.12 Fe2O3 0.05~0.30 Nd2O30~0.4 Cr2O30~0.0100 MnO2O ~ 0.5 V2O50.0001~0.0100.
[0076] A third preferred glass-ceramic composition for the product of the present invention is based on oxides and consists essentially of the following, in weight percent: Li2O 2.5~5 ΣNa2O+K2O 0.1~<3 MgO 0~2.8 ΣCaO+SrO+BaO 0~4 ZnO 0.1~1.9 B2O30~3 Al2O3 18~24 SiO260~70 TiO2 2.5~<4 ZrO2 0.3~2.0 SnO2 0.05 ~ <0.6 P2O50~4 MoO30.0015~0.1 Fe2O3 0.06~0.20 Nd2O30 ~ 0.2 Cr2O3 0.0005~0.0090 MnO2 0.001~0.1 V2O50.0005~0.0080.
[0077] A fourth preferred glass-ceramic composition for the product of the present invention, in weight percent based on oxides, essentially consists of the following: Li2O 3~4.5 ΣNa2O+K2O 0.1~<3 MgO 0~2.8 ΣCaO+SrO+BaO 0~4 ZnO 0.5~1.8 B2O30~3 Al2O3 19~23 SiO260~68 TiO2 2.8~3.9 ZrO2 0.5~1.5 SnO2 0.05 ~ <0.6 P2O50~4 MoO30.020~0.080 Fe2O3 0.007~0.15 Nd2O30 ~ 0.06 Cr2O3 0.0010~0.0060 MnO2 0.005~0.1 V2O50.0010~0.0050.
[0078] A fifth preferred glass-ceramic composition for the products of the present invention is an oxide-based composition, consisting essentially of the following, in weight percent: SiO258~72 Al2O3 16~26 Li2O 1.0~5.5 TiO2 2.0 ~ <4.0 ZnO 0~<2.0 MoO30.005~0.12 ZrO2 / TiO2 0.1~0.67 (V2O5+Cr2O3) / MoO3 0.005~0.5 MoO3 / TiO2 > 0.002 ~ < 0.050 Li2O + SnO2 < 5.8.
[0079] Particularly advantageous properties can be achieved when a fifth preferred composition is selected within the following range: SiO258~72 Al2O3 16~26 Li2O 1.0~5.5 TiO2 2.0 ~ <4.0 ZnO 0~<2.0 MoO30.005~0.12 ZrO2 / TiO2 0.15~0.4 (V2O5+Cr2O3) / MoO3 0.01~0.2 MoO3 / TiO2 > 0.004 ~ < 0.040 Li2O + SnO2 < 5.0.
[0080] More specifically, particularly advantageous properties can be achieved when the fifth preferred composition is selected within the following range: SiO258~72 Al2O3 16~26 Li2O 1.0~5.5 TiO2 2.0 ~ <4.0 ZnO 0~<2.0 MoO30.005~0.12 ZrO2 / TiO2 0.2~0.33 (V2O5+Cr2O3) / MoO3 0.03~0.15 MoO3 / TiO2 > 0.008 ~ < 0.030 Li2O + SnO2 < 4.5.
[0081] The phrase "essentially composed of ~" means that the listed components are intended to make up at least 96% by weight, preferably at least 98% by weight, of the entire composition.
[0082] These glass-ceramics optionally contain up to 2.0% by weight of chemical clarifiers such as As2O3, Sb2O3, and CeO2, as well as clarifying additives such as manganese oxide, sulfate compounds, and halides (F, Cl, Br, I). An example of a halide is the use of NaCl as a batch feedstock for introducing Na.
[0083] For reasons of environmental and workspace safety, it is preferable to avoid using toxic or undesirable raw materials as much as possible. Therefore, glass-ceramics should be free from environmentally harmful substances such as arsenic (As), antimony (Sb), cadmium (Cd), lead (Pb), cesium (Cs), rubidium (Rb), hafnium (Hf), halides, and sulfur (S), except for unavoidable impurities in the range of preferably 0 to less than 0.5 weight percent, more preferably less than 0.1 weight percent, and very preferably less than 0.05 weight percent. The weight percentage values here are also based on the oxide-based glass composition.
[0084] Each of the preferred compositions 1 to 4 described may further have a MoO3 / TiO2 ratio of 0.002 to 0.050, preferably 0.004 to 0.040, and more preferably 0.008 to 0.030.
[0085] Each of the preferred compositions 1 to 4 described may additionally, or instead, have a ZrO2 / TiO2 ratio of 0.1 to 0.67, preferably 0.15 to 0.4, and more preferably 0.2 to 0.33.
[0086] Each of the preferred compositions 1 to 4 described may additionally, or instead, have a ratio of (V2O5 + Cr2O3) / MoO3 of 0.005 to 0.5, preferably 0.01 to 0.2, and more preferably 0.03 to 0.15.
[0087] In industrially used batch raw materials, compounds of multiple elements, such as alkali metals like Rb or Cs, or elements like Mn or Hf, are common impurities. Other compounds, such as those of elements B, Cl, F, W, Nb, Ta, Y, rare earth elements, Bi, Co, Cu, Cr, and Ni, can also typically be present as impurities in industrially used batch raw materials, typically in the ppm range. 1000 ppm is equivalent to 0.1% by weight.
[0088] Additional coloring components such as CoO, CuO, or NiO may be present, provided they do not adversely affect the coloration of the glass-ceramic. As a result, the glass-ceramic preferably contains 0 to 250 ppm, preferably 0 to 100 ppm, more preferably 0 to 50 ppm of CoO, 0 to 250 ppm, preferably 0 to 100 ppm, more preferably 0 to 50 ppm of CuO, and 0 to 250 ppm, preferably 0 to 100 ppm, more preferably 0 to 50 ppm of NiO. Even more preferably, the glass-ceramic is free of CoO, CuO, and NiO, except for unavoidable impurities. Typical impurities of these components are in the single-digit ppm range.
[0089] Manufacturing can generally be carried out using either naturally occurring raw materials, chemically processed or synthesized raw materials, or mixtures thereof. Naturally occurring raw materials are generally cheaper than chemically processed or synthesized raw materials. However, due to typically high levels of impurities, the available natural raw materials are limited. Examples of naturally occurring raw materials include quartz sand, stearate, and feldspar. The amount of impurities in these cases can vary greatly depending on the type and origin of the raw material. For example, both stearate and feldspar are primarily composed of lithium oxide, aluminum oxide, and silicon oxide. Due to the crystalline structure and geochemical properties necessary for the formation of stearate and feldspar, respectively, stearate contains considerably more iron oxide impurities than feldspar. Furthermore, stearate from different mines, and even from different batches of the same mine, may contain a wide variety of iron oxide impurities.
[0090] Chemically processed or synthetically produced raw materials generally contain only very small amounts of impurities. Furthermore, these impurities are relatively constant. Therefore, they vary only to a very small extent between different batches. This is advantageous for planning molten glass batches, as there is virtually no need to compensate for batch-to-batch variations. Examples of commonly processed or synthetic raw materials are lithium carbonate or titanium dioxide powder.
[0091] Typical trace element impurities in the technical raw materials used are usually up to 200 ppm of B2O3, 30 ppm of Cl, 1 ppm of CoO, 3 ppm of Cr2O3, 200 ppm of Cs2O, 3 ppm of CuO, 200 ppm of F, 400 ppm of HfO2, 3 ppm of NiO, 500 ppm of Rb2O, and 1-15 ppm of V2O5.
[0092] Preferably, the glass-ceramic thickness is 1 to 15 mm, preferably 2 to 10 mm, and more preferably 3 to 6 mm. A thickness of about 4 mm is economically very important as it has been developed to become the de facto standard for many applications such as stovetops, stove viewing windows, or baking oven doors.
[0093] Glass-ceramics may have flat surfaces on both sides. Here, "flat" specifically means that they may have flat rolled, floated, or polished surfaces. The advantage of glass-ceramics with flat surfaces is that light-emitting displays can be perceived through the glass-ceramics, particularly without distortion. Alternatively, glass-ceramics may have a structure with numerous bumps on the side opposite to the surface being used. For example, glass-ceramic stoves often have a structure with numerous bumps on their underside, which contributes to improved mechanical robustness. In this context, the "surface being used" is the glass-ceramic surface facing the user of the product. In the case of a stove, this is the top surface.
[0094] In the case of glass-ceramics with numerous nodules, a coating of a transparent material may be present on the molten surface. The refractive index of this material needs to be very close to that of the glass-ceramics in the visible wavelength range of 380 nm to 780 nm. At a wavelength of 550 nm, the difference from the refractive index of the glass-ceramics should preferably be 0.2 or less, more preferably 0.1 or less. An exemplary material having these properties is silicone resin. To maximize transmittance, the silicone resin is preferably used in an uncolored state. However, if coloring of the coating for a light scattering effect is desired, pigments or dyes may be added as needed. The coating can fill the valleys between the nodules at least partially, preferably completely. Due to its immersion effect, this type of coating can reduce, and even level out, the optical distortion of transmitted light caused by the lens effect of the nodules.
[0095] Alternatively, a transparent film can be bonded to the bumps, which also corrects optical distortion. Suitable films for this purpose are transparent and have sufficient temperature stability for use. The refractive index of the film at a wavelength of 550 nm should preferably be less than 0.2, more preferably less than 0.1, from the refractive index of the glass-ceramic. An example of a suitable film is a polycarbonate film bonded to a glass-ceramic surface with numerous bumps by an acrylate adhesive, more specifically in the form of an acrylate film. Due to its high transmittance and thermal stability, a polycarbonate film bonded using an acrylate adhesive is particularly suitable for the display area of a stove. Other examples of suitable films are polyethylene, polyester, or polyethylene naphthalate films. These films can also be similarly fixed to glass-ceramic by an acrylate adhesive, more specifically an acrylate film. The use of other adhesives, more specifically other adhesive films, is also possible. Any adhesive that adheres to glass and plastic surfaces, is transparent, and has sufficient temperature stability for use is generally suitable. At a wavelength of 550 nm, the refractive index of the adhesive must be less than or equal to 0.2, more preferably less than or equal to 0.1, the refractive index of the glass-ceramic material. An example of a suitable alternative adhesive is a silicone-based adhesive.
[0096] As an alternative, thin-walled or ultra-thin-walled glass can be used instead of film. In the case of polymer films, regardless of the properties of the adhesive, the adhesive can partially or completely fill the valleys of the bumps. In the case of thin-walled or ultra-thin-walled glass, unlike polymer films, the glass cannot conform to the shape of the bumps, so the adhesive needs to completely fill the valleys of the bumps.
[0097] In one advanced form of the present invention, an optical filter may be provided in the product, for example, to adjust the color trajectory of a light-emitting display. For example, in a single operating unit, multiple white light sources, particularly LEDs, with different structures and therefore different light colors may be used. In this case, the light colors of the different light sources can be adjusted relative to each other by a targeted filter.
[0098] For example, when using a light-emitting element where the light, after passing through glass-ceramic without a color filter, is within the white region A1, other color filters can also be provided in the product to cause the light emission phenomenon outside the white region A1. For example, after passing through such a color filter and glass-ceramic, white light can be converted into colored light, such as blue, red, or green light, or virtually any other desired color. Such color filters preferably have a C value greater than 0.08, preferably greater than 0.16, and more preferably greater than 0.24, in order to express particularly high-saturation colors. * It has.
[0099] These types of filters can exist, for example, in the form of layers coated by printing or other methods, or in the form of plates or films formed by pressing or lamination. Filters in layer form can be manufactured by common processes. These include, for example, printing, more specifically screen printing, flexographic printing, inkjet printing, slot die coating, knife coating, and vacuum coating processes, more specifically plasma CVD and sputtering. Filters can be laminated, printed, or coated directly onto the glass-ceramic or indirectly onto a carrier such as a film or plate, which is then placed between the light-emitting element and the glass-ceramic.
[0100] In a preferred embodiment, the product, in addition to the glass-ceramic, has means for reducing luminous transmittance. Such means may specifically be a coating applied to the glass-ceramic, and a bonded or pressed film or bonded or pressed plate. Such means are particularly preferably positioned on the glass-ceramic surface opposite to the user in the intended use.
[0101] This type of means for reducing luminous transmittance, along with glass-ceramics, has a luminous transmittance of less than 0.5%, preferably less than 0.1%, more preferably less than 0.01%, and even less than 0.001%. When this means takes the form of a metal foil, particularly an aluminum foil, having a thickness of at least 100 μm, luminous transmittances significantly lower than 0.001% can also be achieved. Such low transmittance values can also be achieved by coatings based on sol-gel, silicone, or enamel, using the corresponding pigments and layer thicknesses. For example, sputtered layers of metals such as aluminum, silver, or stainless steel can also have a correspondingly low transmittance with sufficient layer thickness.
[0102] This type of means for reducing luminous transmittance preferably has at least one cutout through which light can pass. This type of cutout can, for example, form a window for a light-emitting display. Alternatively, such a cutout can take the form of, for example, a symbol, a letter, a geometric shape, or a number. When such a cutout is illuminated from behind by a light-emitting element, the user of the product can, for example, recognize a light-emitting symbol that is only faintly or not recognizable when the light-emitting element is switched off. This improves operational safety because the user can always recognize the activated letters or symbols well and therefore is not likely to confuse them with unactivated letters or symbols.
[0103] If the means for reducing luminous transmittance takes the form of a coating, such cutouts do not need to have such a coating from the beginning, or the coating can be removed again at this point. This can be done, for example, by a laser, more specifically by a CO2 laser or an ultrashort pulse laser. Removal can also be done wet chemically. If a film or plate is used, for example, the cutouts can be created by cutting out the corresponding portion of the film or plate.
[0104] In addition to the cut-out sections, means for reducing luminous transmittance can be placed across the entire area of the cover, or only in a portion of it. To achieve a particularly high reduction in luminous transmittance, two or more of these means can be placed sequentially, directly or indirectly.
[0105] In a more preferred embodiment, the product has at least one diffuser. During the process of the intended use, the diffuser is positioned on the product or glass-ceramic surface opposite the viewer. The diffuser here has a luminous transmittance of at least 10% and, by its structure, is a means capable of converting directional light passing through the diffuser into diffused light at least proportionally by light scattering.
[0106] The diffuser can take the form of, for example, a coating, film, or plate. Light scattering can be caused, for example, by appropriately sized particles present in the coating, film, or plate. Such particles may have a size on the order of the wavelength of visible light or smaller. Furthermore, such particles have a refractive index different from that of the surrounding coating, film, or plate. Such particles may consist of, for example, TiO2, or contain TiO2. It is particularly preferable that the particles are spatially uniformly distributed within the coating, film, or plate.
[0107] The scattering effect of the diffuser can instead be achieved, for example, by a region having a sufficiently large roughness on the surface of a glass-ceramic, coating, film, or plate. A surface having a large roughness can be produced, for example, by a polishing process such as sandblasting or by an etching process. A sufficiently high roughness in this context means an average roughness R of 100 nm to 10 μm, preferably 200 nm to 2 μm, more preferably 500 nm to 1 μm. a means.
[0108] The effect of this type of diffuser is that the light from the light-emitting element directed towards the diffuser produces a substantially uniform illumination appearance. This applies particularly to light-emitting elements having point-based lighting means such as LEDs.
[0109] The diffuser can also be arranged, in particular, in the region of the cut-out of the means for reducing the visual transmittance. There, it may partially or completely overlap the cut-out. This advantage is that when the cut-out is illuminated by the lighting element, it can be illuminated particularly uniformly.
[0110] In the case of a combination of a diffuser and means for reducing the visual transmittance, the diffuser can be arranged, for example, between the glass-ceramic and the means, between the means and the light-emitting element, or between two means for reducing the visual transmittance. In that case, it may overlap with one or more means for reduction in each case. When arranged between two reduction means, the two means have overlapping cut-outs and the diffuser needs to be arranged at least partially in the overlapping region.
[0111] The product may have further coatings on the glass-ceramic. These include, for example, decorative coatings, layers for marking specific areas, text, or symbols, scratch-resistant layers, anti-reflective layers, refractive layers, conductive layers, layers for enhancing infrared reflection, layers for improving cleanability, anti-glare layers, anti-fingerprint layers, antimicrobial layers, or combinations thereof. Depending on the implementation, such layers may be placed on one or both sides of the glass-ceramic, across the entire surface, or on only a portion of the surface. Such coatings may instead be individual layers or stacks of multiple layers placed on top of or behind each other.
[0112] In a preferred embodiment, the product may have a number of different lighting systems, or may be combined with them. Such lighting systems can be used, for example, for decorative lighting or to generate light-emitting displays. These may employ multiple different technical lighting solutions. These may have, for example, LEDs, OLEDs, laser diodes, projectors, optical waveguides, pixel-based displays, particularly LCDs or AM-OLEDs, segment displays, more specifically 7-segment displays, and / or point-like, close-range, or wide-area light-emitting elements. The light-emitting elements may have a single, unchangeable color. They can instead allow for changeable colors, mixed variations made from different colors, more specifically red, green, and / or blue light, or emit spectrally broad light, more specifically white light. Spectrally broad emission refers to an emission spectrum with a full width at half maximum (FWHM) greater than 50 nm.
[0113] The present invention will be described in more detail with reference to the figures. [Brief explanation of the drawing]
[0114] [Figure 1]Details of the CIE chromaticity diagram in the CIExyY color space include: - the blackbody curve ("BBC"), - the chromaticity coordinates of the light from the standard light source D65 when viewed directly without using glass-ceramics ("D65"), - the positions of the white regions A1 and A2, and - the chromaticity coordinates of the light from the standard light source D65 after passing through the glass-ceramics of Examples 1-16 ("Examples 1-16"). [Figure 2] The positional overview shows the same data as in Figure 1, but it is not detailed and represents the entire CIExyY color space. [Figure 3] This figure shows the relationship between resistivity and AC current frequency at different temperatures. Measurements were performed on glass-ceramics according to Example 17. [Figure 4] This figure shows the relationship between relative permittivity and the frequency of the alternating current at different temperatures. Measurements were performed on glass-ceramics according to Example 17. [Figure 5] This figure shows the relationship between the loss coefficient and the frequency of the alternating current at different temperatures. The measurements were performed on glass-ceramics according to Example 17. [Figure 6] This figure shows the relationship between the relative permittivity of glass-ceramic and temperature for AC frequencies of 1.9 GHz and 5.1 GHz. Measurements were performed on glass-ceramic according to Example 17. [Figure 7] This figure shows the relationship between the loss coefficient and temperature of glass-ceramic materials for AC frequencies of 1.9 GHz and 5.1 GHz. Measurements were performed on glass-ceramic materials according to Example 17. [Figure 8] This figure shows the relationship between the relative permittivity of glass-ceramics and temperature for AC frequencies of 1 MHz, 1.9 GHz, and 5.1 GHz. Measurements were performed on glass-ceramics according to Example 17. [Figure 9] This figure shows the relationship between the loss coefficient and temperature of glass-ceramic materials for AC frequencies of 10 kHz, 100 kHz, 1 MHz, 1.9 GHz, and 5.1 GHz. Measurements were performed on glass-ceramic materials according to Example 17. [Figure 10a]This figure shows the spectral transmittance of the glass-ceramic material of the present invention (reference symbol 1) with a thickness of 4 mm in the wavelength range of 380 nm to 780 nm. Furthermore, Figure 10a also shows the spectral transmittance of the same glass-ceramic material with an additional scratch-resistant layer (reference symbol 2) with a thickness of 4 mm in the wavelength range of 380 nm to 780 nm. [Figure 10b] This figure shows the same data as Figure 10a, but the wavelength range is 250 to 2500 nm.
[0115] The blackbody curves BBC in Figures 1 and 2 illustrate the color locus of light emitted by a blackbody radiator at different radiator temperatures when viewed directly (without glass-ceramics). Since the sun is a blackbody radiator, the light whose color locus lies on the BBC curve is perceived as particularly white, natural, and pleasant.
[0116] When viewed directly (without glass-ceramic), the light from the standard light source D65 is located at the color coordinates x=0.3127, y=0.3290. When the D65 standard light passes through an absorptive glass-ceramic, the color trajectory of the light may shift as a result of absorption by the glass-ceramic. The D65 standard light is roughly equivalent to a blackbody radiator with a temperature of approximately 6500K.
[0117] For all of Examples 1-17, the color trajectory of the standard light source D65 as it passes through the corresponding sample shifts minimally along the BBC. Examples 1-4 are located almost exactly on the BBC. For all examples, the color trajectory is located within region A1. Examples 1-4 are also within A2. Example 5 is located slightly below the BBC and just outside A2. Therefore, all examples exhibit very chromatically neutral behavior with respect to transmitted light. The color shift is minimal.
[0118] Examples 1 to 17 are described in more detail with reference to Table 1. Examples 1 to 17 are glass-ceramics suitable for use in the products of the present invention. Comparative Example V1 is a glass-ceramic that is not suitable for the present invention.
[0119] The crystallizable starting glass for the examples in Table 1 was manufactured in a plant for the industrial production of LAS glass-ceramics. Knowledge sources regarding melting operations for the industrial production of LAS glass-ceramics include European Patent No. 2226303 and "Allgemeine Technologie des Glases, Grundlagen des Schmelzens und der Formgebung" [General Glass Technology, Principles of Melting and of Shaping], Prof. Dr. HA Schaeffer, Erlangen, September 1985. The crystallizable starting glass is also referred to as green glass below.
[0120] Manufacturing was carried out using batch raw materials that are common in the industry. For example, these include: [Table 4]
[0121] The melting unit used was a continuously operating hybrid tank equipped with an oxygen combustion burner and additional electric heating. However, it is equally conceivable to use a continuously operating all-electric tank or a tank heated solely with fossil fuels as the melting unit. In the case of a fossil fuel-heated tank, the fuel used may instead be a mixture of fossil fuels and hydrogen, or a hydrogen-based fuel that does not contain fossil components. The use of synthetic fuels is also conceivable.
[0122] In this context, "continuous operation" means that batches are continuously supplied to the melting unit at one end, and molten glass is continuously drawn out at the opposite end.
[0123] In contrast to this, there are discontinuously operating melting units. In discontinuously operating units, batches are placed in a sufficiently cold crucible. When the crucible is heated, the batches melt, forming molten glass. The molten glass is then poured out of the crucible and subjected to hot forming. When the crucible has cooled sufficiently again, it is refilled with batches, and a new melting operation can be performed. Therefore, glass can only be extracted discontinuously (in batches) from this type of unit.
[0124] The specific melting capacity of a unit represents the number of metric tons of glass that can be produced per day, based on the unit's base area. This is reported in units of metric tons per square meter per day (i.e., t / (m²). 2 d)).
[0125] The base area of a unit is the product of the distance between the batch inlet at the front of the unit and the distributor at the rear of the unit, in other words, the product of the total length of the molten glass within the unit and the width of the molten glass within the unit. For example, a unit defined in this way, with a width of 8m and a length of 15m, has a base area of 120m². 2 It has a base area of approximately 50-250 m². In glass-ceramic manufacturing, the base area is approximately 50-250 m². 2 The unit is common.
[0126] Another factor that affects specific melting performance is how the unit is operated. The higher the operating temperature, the faster the thermal processes such as melting and clarifying of the glass molten material proceed. As a result, more glass can be extracted from the unit at higher temperatures.
[0127] Operating a unit with very low specific melting capacity compromises the economics of the manufacturing operation. Operating at very high specific melting capacity carries the risk of high throughput negatively impacting glass quality. This can occur, for example, if the molten glass has a short residence time within the unit, preventing the complete melting process, or if there isn't enough time available for clarification.
[0128] The glass-ceramic material of the present invention is, for example, 0.3t / (m 2 d) ~1.5t / (m 2 d) Preferably 0.4~1.2t / (m 2 d), more preferably 0.5~1.1t / (m 2 It can be manufactured using a unit having the specific melting performance of d).
[0129] Surprisingly, compared to glass-ceramics that melt discontinuously in a crucible, at least 0.3 t / (m 2 d) and a maximum of 1.5t / (m 2 Glass-ceramics produced in a continuous operation melting unit having the specific performance of d) exhibit improved properties, particularly excellent color neutrality and reduced need for coloring components in the glass-ceramic composition.
[0130] The manufacturing processes observed in the examples from Table 1 are as follows: • Batch preparation and introduction into the tank. To improve melting behavior, fragments from a closed circulation of fragments in the tank, or optionally fragments from a recycling circulation, are typically added to the batch. • Batch melting. • Clarification of the glass melt at a glass melting temperature of at least 1550°C, preferably 1600°C, more preferably 1650°C. The upper limit of the clarification temperature usually depends on the temperature stability of the tank material. The clarification temperature is typically below 1850°C, preferably below 1800°C, more preferably below 1750°C. Temperatures above 1700°C usually require the use of additional high-temperature clarification equipment. This means additional energy consumption for manufacturing, but in certain situations, this can be highly competitive as a result of better specific melt performance and improved glass quality. For example, cooling of molten glass to a temperature suitable for hot forming such as rolling. • Hot forming operations, such as rolling glass strips up to a thickness of, for example, 4 mm. • Cooling to room temperature, separation into individual plates, and stacking.
[0131] The examples in Table 1 are 1 t / (m 2 The materials were manufactured with the specific melting performance described in d). Each example was manufactured in the form of a rectangular plate with dimensions of 520 × 590 × 4 mm.
[0132] The water content of the crystallizable glass for glass-ceramic production manufactured in this manner is preferably 0.01 to 0.09 mol / l, depending on the selection of batch raw materials and the operating conditions in the melting stage. A method for determining the water content is described, for example, in European Patent No. 1074520. The water content can be adjusted to match the selection of batch raw materials and process conditions.
[0133] Samples 1-17 are ceramicized in a continuous furnace using the following process: a) Heat from room temperature to 740°C at a heating rate of 30K / min. b) Heat from 740°C to 825°C at a heating rate of 6K / min. c) Heating rate of 18K / min, raise temperature from 825°C to 930°C. d) Hold at a maximum temperature of 930°C for 6 minutes. e) Cool the sample to 800°C at a cooling rate of 13K / min, then rapidly cool it to room temperature by removing it from the furnace.
[0134] Samples 18-24 are ceramicized in a continuous furnace using the following process: a) Heat from room temperature to 740°C at a heating rate of 30K / min. b) Heat from 740°C to 825°C at a heating rate of 6K / min. c) Heat from 825°C to 930°C at a heating rate of 15K / min. d) Hold at a maximum temperature of 926°C for 6 minutes. e) Cool the sample to 800°C at a cooling rate of 12K / min, then rapidly cool it to room temperature by removing it from the furnace.
[0135] It is known that the temperature, holding time, and heating rate during ceramicization can be adjusted to optimize the properties of the resulting glass-ceramic, starting from the examples shown above. In particular, it may be advantageous to select higher heating / cooling rates than those shown in the examples. However, the heating / cooling rates should not fall below the following values: 20 K / min in step a), 2 K / min in step b), 8 K / min in step c), and cooling at a rate of at least 8 K / min in step d). Higher rates are beneficial not only for the physical properties but also for the cycle time of the ceramicization process. The temperature in step d) can be varied, for example, in the range of 890–940°C.
[0136] In reality, the achievable heating rate depends on both the shape / thermal mass of the plate for ceramicization and the available heating unit.
[0137] Plates ceramicized by this method may have a glassy, amorphous lithium-reduced surface zone on their surface. Such zones are known, for example, from International Publication No. 2012019833. These improve the glass-ceramic's resistance to chemical attack. The glassy zone has a thickness of 20 to 5000 nm, preferably 30 to 3000 nm, and more preferably 50 to 1500 nm. The glassy zone can be removed from the glass-ceramic surface after ceramicization by polishing.
[0138] Unless otherwise specified, typical trace element impurities in the technical raw materials used are up to 200 ppm B2O3, 30 ppm Cl, 1 ppm CoO, 3 ppm Cr2O3, 200 ppm Cs2O, 3 ppm CuO, 200 ppm F, 400 ppm HfO2, 3 ppm NiO, 500 ppm Rb2O, and 5 ppm V2O5.
[0139] Table 1 shows the compositions of Examples 1-17 and Comparative Example V1, as well as specific selected properties after ceramicization. Aside from common impurities, the examples do not contain Sb2O3 or As2O3. All examples contain a corresponding amount of MoO3 as the main colorant.
[0140] Comparative Example V1 was manufactured using a discontinuous process, rather than the continuous melting unit process described above in Examples 1-17. In each case, the crystallizable starting glass was melted at 1620°C for 4 hours from technical batch raw materials common in the glass industry. After melting the batch in a sintered silica glass crucible, the melt was poured into a Pt / Rh crucible containing a silica glass crucible inside and homogenized by stirring at 1600°C for 60 minutes. Following this homogenization, the glass was clarified at 1640°C for 2 hours. Subsequently, a sample of approximately 120 × 140 × 30 mm was prepared. 3 Pieces of the specified size were cast and cooled in a cooling oven starting at 640°C to room temperature to distribute stress. The castings were divided into sizes necessary for investigation and sizes necessary for ceramicization. Ceramicization was carried out using the same process as used for ceramicization in Examples 1-17.
[0141] Despite a relatively high MoO3 content of 0.11 wt%, the comparative example exhibits a luminous transmittance exceeding 4% at a thickness of 4 mm. As a result of this high luminous transmittance, the opacity of this glass-ceramic is low, making it unsuitable for use in the product of the present invention. Furthermore, the comparative example has an undesirably high ZnO content exceeding 2 wt%.
[0142] The comparative example has a temperature T (pO2 = 1 bar) of less than 1550°C. Therefore, it contains a relatively large amount of dissolved oxygen in the glass-ceramic. In comparison, Examples 1-5 have higher temperatures T (pO2 = 1 bar) in the range of 1592°C to 1633°C. Therefore, they contain less dissolved oxygen than Comparative Example V1.
[0143] Examples 1-17 contain 7-35 ppm of V2O5 and 10-41 ppm of Cr2O3. Therefore, as is clear from Figure 1, it is possible to make the color trajectory of the transmitted light from the standard light source D65 very accurately within the white region A1 to the desired value. Comparative example V1 contains neither V2O5 nor Cr2O3.
[0144] Table 1 lists the spectral transmittances at various wavelengths in the visible and near-infrared spectral ranges. All reported values are based on a glass-ceramic thickness of 4 mm. These values provide evidence of a transmittance profile favorable to the product of the present invention, having low transmittance in the visible spectral range of 380–780 nm and high transmittance in the near-infrared range of 780–4000 nm. Due to this type of profile, glass-ceramics are suitable for manufacturing cover plates that transmit thermal or IR radiation for optical communications or sensor technology while preventing visibility through the plate.
[0145] These values clearly show that the transmittance of Comparative Example V1 at a specific wavelength is significantly higher than that of Examples 1 to 17.
[0146] The color coordinates in the CIExyY color space (1931, 2°) of light from a standard light source D65 after passing through a 4 mm thick sample are also shown in Table 1. The Y coordinate is the luminous transmittance τ according to DIN EN 410. vis It is identical to [the other one].
[0147] In the examples, thermal expansion was determined in the temperature range of 20°C to 700°C. All examples were 1 × 10⁻⁶. -6 They have values significantly lower than / K. Based on this low expansion, these glass-ceramics are particularly suitable for use in products such as stoves that are subjected to high-temperature variable loads or high local temperature gradients.
[0148] X-ray diffraction confirmed that all examples contained a high-quartz solid solution ("HQSS") as the main crystalline phase. This is evident from the fact that, at a thickness of 4 m, the examples showed virtually no visible scattering to the naked eye.
[0149] Based on Example 17, the electrical properties of the glass-ceramic were typically investigated for all examples. The results are shown in Figures 3 to 9. The glass-ceramic exhibits electrical properties typical of LAS glass-ceramic. Resistivity R with respect to current spec The resistivity decreases as the temperature of the glass-ceramic increases. Furthermore, the resistivity to alternating current decreases as the frequency of the alternating current increases. In this regard, Figure 3 shows resistivity measurement data recorded at temperatures from -15°C to 350°C and frequencies from 10 kHz to 40 MHz. The value is 5.5 * 10 4 Ωcm to 1.8 * 10 9 It extends beyond 10 to the power of 4, up to Ωcm. This can probably be explained by the change in the mobility of charge carriers in glass-ceramics under the corresponding conditions.
[0150] Therefore, the electrical properties of the glass-ceramic also change, especially with respect to the AC voltage that may exist between the upper and lower surfaces of the glass-ceramic. These properties are represented here by the relative permittivity ε of the glass-ceramic. rThe relative permittivity and loss factor tan(δ) are quantified by measuring these parameters, and these are illustrated in Figures 4–9 as functions of the frequency of the applied AC voltage and the temperature of the glass-ceramic stove. Figures 4 and 5 show the frequency dependence of relative permittivity and loss factor for various temperatures that occur particularly in cooking applications of glass-ceramic stoves, over the frequency range of 10 kHz to 40 MHz. Figures 6 and 7 show the temperature dependence of relative permittivity and loss factor at frequencies of 1.9 GHz and 5.1 GHz. These frequencies represent important frequency ranges for microwave heating applications and wireless signal networks such as WLAN / WiFi. Figures 8 and 9 show temperature dependence similar to Figures 6 and 7, but are extended to include exemplary frequencies in the range of 10 kHz to 40 MHz, and here particularly to include the temperature range up to 350°C, which is typical for cooking applications.
[0151] AC voltage can be useful as a measurement signal or for technical applications such as power transmission. Particularly in the frequency range of 10 kHz to 40 MHz, measurements can provide, for example, capacitive touch sensors, or capacitive or non-capacitive temperature measuring devices, especially those with temperature-dependent electrical properties. A particularly important factor for touch sensors is the dielectric constant at room temperature. The exemplified dielectric constant value at 25°C, in the range of 7.9 to 8.3, is stable across the frequency range of 10 kHz to 40 MHz (Figure 4). Glass-ceramics are particularly suitable for capacitive touch sensors because they exhibit significantly higher dielectric constants than other materials, which typically have low dielectric constants. For comparison, other materials include plastics (2-4), natural materials such as wood and paper (1-4), or glass (around 6-7).
[0152] The temperature dependence of the relative permittivity and loss coefficient (Figures 8 and 9), which is particularly pronounced in the low frequency range (10 kHz to 40 MHz), can be used, for example, in capacitive or inductive temperature measurements. Capacitive temperature measurements can be performed, for example, between a sensor electrode under glass-ceramic and the bottom of a pot on glass-ceramic. The relative permittivity related to capacitive measurements changes approximately threefold, from 8.1 to 25.8 between 25°C and 350°C, as an example, and this can be converted into a change in the electrical signal in known ways. Similarly, the temperature-dependent loss coefficient can be used in inductive temperature measurements. For example, the transmission loss between an emission coil under glass-ceramic and a sensor coil in a cooking container on glass-ceramic changes approximately 300 times, from 0.03 to 8.9 between 25°C and 350°C, and 5 times, from 0.05 to 0.25 between 50°C and 150°C, at a signal frequency of 10 kHz. The sensor coil beneath the glass-ceramic layer also responds sensitively to temperature-dependent changes in the electrical properties of the nearby glass-ceramic material due to self-induction.
[0153] The temperature-dependent change in the loss coefficient is also relevant to induction heating, such as that seen in induction cooktops. Typical operating frequencies here are 10 kHz to 100 kHz. The increase in the loss coefficient with temperature in this frequency range (Figure 9) results in a decrease in power transfer to the cooking container and / or a measurable increase in power loss in the intrinsic circuit of the induction heating. This can also be indirectly used to measure the temperature of the cooking container.
[0154] Additional applications where the loss factor plays a particularly important role in relation to power transmission at different frequencies include inductive charging devices for mobile terminal devices on glass-ceramic cooktops or worktops, or applications in the field of electric vehicles. Galvanically insulated signal transmission through glass-ceramics used as partitions or protective walls in biologically, chemically, or physically (radially) isolated and protected areas is also subject to the electrical properties described exemplified above.
[0155] As a further example, a 4 mm glass-ceramic layer according to Example 17 was coated with a scratch-resistant layer. This layer was manufactured by reactive medium-frequency sputtering as described in International Publication No. 2014135490. This coating is an X-ray amorphous AlSiN layer with an Al:Si ratio of 50:50 at%. The thickness of the layer is approximately 1200 nm. Figures 10a and 10b plot the spectral transmittance of uncoated glass-ceramic (reference symbol 1) and coated glass-ceramic (reference symbol 2) against the wavelength of light (nm) for comparison. Compared to the uncoated glass-ceramic, only interference modulation of transmission from the substantially transparent coating is present. As a result, the luminous transmittance is slightly reduced. The reduction is approximately 8% relative and approximately 0.2% absolute. The color trajectory of light from a standard light source D65 changes only slightly due to the coating and is therefore imperceptible to the naked eye. The color difference of transmitted light can be calculated by the following formula:
number
[0156] In this equation, x GK / y GK This is the color coordinate of light from a standard light source D65 after passing through uncoated glass-ceramic (here x GK =0.3184, y GK =0.3270), and x GK+S / y GK+S This is the color coordinate after passing through the coated glass-ceramic (here x GK+S =0.3202, y GK+S (=0.3284). Therefore, in the coating shown in Figure 3, ΔC is only 0.002, and thus imperceptible to the human eye.
[0157] For comparison, we can again refer to the color coordinates of the light from the standard light source D65 when viewed directly, i.e., without the glass-ceramic coating: x=0.3127, y=0.3290. Therefore, in this case, the color of the light from the standard light source D65 does not shift significantly, neither due to the glass-ceramic coating itself nor due to the combination of glass-ceramic and scratch-resistant coating.
[0158] The product of the present invention can be used in a variety of applications.
[0159] In one embodiment of the present invention, the product can be used as a cooking plate in a kitchen appliance.
[0160] In another embodiment, the product of the present invention can be used to cover the user interface of a control panel for controlling at least one home appliance, more specifically a cooking appliance, a baking oven or refrigerator or a ventilation fan.
[0161] In one evolution of this embodiment, the control panel can be configured to control multiple appliances, such as a cooking appliance, a baking oven, and a ventilation fan. The ventilation fan may be integrated in the form of a downdraft ventilation fan with a cooking appliance having a corresponding glass-ceramic cooking plate. In this case, for this purpose, the product or glass-ceramic may have a cutout into which the downdraft ventilation fan can be inserted. In a further embodiment, the product can be designed as a cover for a ventilation fan, more specifically a downdraft ventilation fan. Particularly in modular cooking systems, the downdraft ventilation fan may be designed as an independent module without cooking function. However, since such modules must be suitable for use in combination with modules that have cooking function, they must also meet the same very strict general requirements in terms of thermal and chemical stability. Furthermore, such modules may also have a user interface for controlling the downdraft removal device. This type of user interface also needs to satisfy the above-mentioned objective regarding color-neutral display.
[0162] In further embodiments, the product can be designed as a surface for a group of ventilation fans. In this embodiment, the surface finish of the stovetop of the cooking appliance and the ventilation fan can be particularly aesthetically appealing if they feature the same glass-ceramic material. This embodiment is particularly advantageous if the ventilation fan features a user interface located behind the glass-ceramic material for controlling the ventilation fan, or a user interface for controlling the ventilation fan and the cooking appliance together.
[0163] In baking ovens, particularly pyrolysis ovens, the product of the present invention is used as part of the door glass.
[0164] In further embodiments, the product of the present invention can be used in kitchen fixtures, more particularly in kitchen cabinet articles, as a worktop on a countertop.
[0165] In another embodiment, the product of the present invention can be used as a splash guard for kitchens. Therefore, it can be used, for example, as a plate on the back wall of a kitchen, instead of a tiled mirror. It can also be installed as a freestanding splash guard in an island kitchen. This type of splash guard can be permanently installed or designed as a recessed type. Recessed splash guards can be extended to allow for the operation of cooking appliances in order to function as a splash guard. After cooking is finished, they can then be stored, for example, inside the cooking appliance or on the worktop. In this case, it can be particularly aesthetically pleasing if both the cooking plate of the cooking appliance and the splash guard feature the same glass-ceramic material as the product of the present invention. The kitchen worktop may also similarly contain the same glass-ceramic material.
[0166] Kitchen splash guards are regularly subjected to splashes of high-temperature liquids such as saltwater and animal / vegetable oils during cooking. These are also regularly cleaned with chemical cleaning agents. Considering the high thermal and chemical stability of the products of the present invention, they are particularly suitable for use as splash guards in kitchens.
[0167] In another embodiment, the product of the present invention can be used to cover a user interface or as a worktop in laboratory equipment, more specifically in hot plates, ovens, balances, or articles of laboratory equipment, more specifically in ventilation fans, cabinets, or benches.
[0168] In another embodiment, the product of the present invention can be used as a viewing window for a stove for combustion chambers and other high-temperature process chambers, as fireproof glass, as part of a housing for a mobile electronic device, particularly a mobile phone and a tablet computer, as a cover for an IR heating lamp or gas burner, particularly a gas grill, as a privacy screen, or as a cover for an induction charging station for a powered vehicle / automobile, for example, as a cover in the dashboard area or center console.
[0169] Based on its thermochemical stability, the product can be used in indoor and outdoor stoves. Such stoves can be powered by gas, wood, or pellets, for example.
[0170] The high-temperature process chamber may be, for example, a vacuum coating system.
[0171] In grill appliances, a variety of possible applications of the product of the present invention exist. It can be used to provide a protective cover for a gas burner that hides the gas burner when the switch is off, but shows the flame when the switch is on. Since the color of the flame is an important indicator for the proper operation of the grill, the kind of true color representation possible with this product is particularly advantageous for safety of operation.
[0172] This product can also be used as a grill surface, especially for gas, electric, or charcoal grills, or as a viewing window for a grill hood.
[0173] [Table 5-1] [Table 5-2] [Table 5-3] [Table 5-4] [Table 5-5]
Claims
1. 1. An article comprising a transparent body colored glass-ceramic, said glass-ceramic comprising the following components, in weight percent on an oxide basis: Yes 2 58-72, <h2 style=";text-align:left;direction:ltr">Al<h2 style=";text-align:left;direction:ltr"> 2 <h2 style=";text-align:left;direction:ltr"> O<h2 style=";text-align:left;direction:ltr"> 3 <h2 style=";text-align:left;direction:ltr"> 162626 Li 2 O 1.0~5.5、 TO 2 2.0~<4.0, ZnO 0~<2.0, MỏO 3 0.005~0.012 Including, The glass-ceramic has a luminous transmittance τ of 0.5% to 3.5%, preferably 0.8% to 3.2%, more preferably 1.0% to 3.0%, and more particularly 1.2% to 2.8%, based on a thickness of 4 mm. vis having The glass-ceramic has the following coordinates after standard illuminant D65 light passes through the glass-ceramic, based on a thickness of 4 mm: 【Table 1】 A product having a characteristic of having a color locus in the white region A1 in the CIE xyY-2° chromaticity diagram defined by:
2. The glass-ceramic may comprise MoO in an amount of 0.015 wt. % to 0.100 wt. %, preferably 0.020 wt. % to 0.080 wt. %, more preferably 0.030 wt. % to 0.070 wt. %. 3 2. The article of manufacture of claim 1, comprising:
3. The temperature T of the glass-ceramic (pO 2 = 1 bar) is in the range of 1550 to 1700 ° C, preferably in the range of 1560 to 1690 ° C, more preferably in the range of 1570 to 1680 ° C.
4. The glass-ceramic contains TiO in an amount of 2.5 wt.% to <4.0 wt.%, preferably 2.8 wt.% to 3.9 wt.%, more preferably 3.0 wt.% to 3.8 wt.%. 2 3. The product according to claim 1 or 2, characterized in that it comprises:
5. The glass-ceramic contains ZrO in an amount of 0.1% to 2.5%, preferably 0.3% to 2.0%, more preferably 0.5% to 1.5%. 2 2. The article of manufacture of claim 1, comprising:
6. The glass-ceramic has a ZrO 2 / TiO 2 Ratio of TiO 2 and ZrO 2 2. The article of manufacture of claim 1, comprising:
7. The glass-ceramic is V in an amount of 0.0001% to 0.010% by weight, preferably 0.0005% to 0.0080% by weight, more preferably 0.0010% to 0.0050% by weight 2 O 5 and / or Cr in an amount of 0% to 0.0100% by weight, preferably 0.0005% to 0.0090% by weight, more preferably 0.0010 ppm to 0.0060 ppm 2 O 3 and / or Fe in an amount of 0.05% to 0.30% by weight, preferably 0.06% to 0.20% by weight, more preferably 0.07% to 0.15% by weight 2 O 3 2. The article of manufacture of claim 1, comprising:
8. 2. The product according to claim 1, characterized in that the glass-ceramic has a thickness of 1 to 15 mm, preferably 2 to 10 mm, more preferably 3 to 6 mm.
9. The glass-ceramic has a (V 2 O 5 +Cr 2 O 3 ) / MoO 3 Ratio: MoO 3 , V 2 O 5 and Cr 2 O 3 2. The article of manufacture of claim 1, comprising:
10. The glass-ceramic has a MoO of 0.002 to 0.050, preferably 0.004 to 0.040, more preferably 0.008 to 0.
030. 3 / TiO 2 Ratio: MoO 3 and TiO 2 2. The article of manufacture of claim 1, comprising:
11. The composition of the glass-ceramic satisfies the following conditions: Li 2 O+SnO 2 <5.8, preferably <5.0, more preferably <4.5 The product according to claim 1, characterized in that
12. The glass-ceramic has the following coordinates after the standard illuminant D65 light passes through the glass-ceramic, based on a thickness of 4 mm: 【Table 2】 2. The product according to claim 1, characterized in that it has a characteristic of having a color locus in a white region A2 in the CIE xyY-2° chromaticity diagram defined by:
13. The article of manufacture of claim 1, wherein the glass-ceramic is produced in a continuous melting apparatus.
14. 2. Use of a product according to claim 1 in cooking appliances, baking ovens, kitchen fittings, kitchen splash guard plates, indoor stoves, more particularly as an interior or exterior lining or sight glass, outdoor stoves, more particularly as an interior or exterior lining or sight glass, grills, refrigerators, microwave appliances, extractor fan covers or facings, mobile phones, tablet computers, automobiles, laboratory equipment, laboratory fittings, fire protection glass, as sight glass in high temperature process chambers, IR emitter covers, privacy screens, covers of user interfaces of control panels, preferably for controlling at least one household appliance, or covers of induction charging stations.